PENGEMBANGAN LABORATORIUM MIXED REALITY (MR) UNTUK SIMULASI PRAKTIK TEKNIK MESIN BAGI GURU SEKOLAH MENENGAH KEJURUAN (SMK) - Nur Imansyah; Rachmah Agus Putri (Smart Education, 2025)
Abstract: Limited access to laboratory facilities in vocational education, particularly in the field of mechanical engineering, often becomes a major obstacle in providing safe and industry-relevant practical experiences. Vocational high school (SMK) teachers in Bontang face challenges in delivering effective and efficient practice-based learning. This study aims to develop a Mixed Reality (MR) Laboratory as an innovative solution for simulating mechanical engineering practices. The MR Mixed Lab is designed to provide interactive learning experiences through mixed reality technology, enabling teachers to guide students in understanding machine assembly and disassembly concepts without the risk of equipment damage or injury. In addition, MR implementation can reduce operational practice costs and increase the frequency of training within a more realistic learning environment. The research method employed is Research and Development (R&D) with the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The development process involves user needs analysis, system design, creation of interactive 3D models, and effectiveness testing involving vocational school teachers. Data are collected through observation, questionnaires, and interviews to evaluate usability, learning effectiveness, and user engagement. The expected outcome is an MR Lab prototype that is relevant, feasible, and beneficial for vocational education.Â Keywords: Mixed Reality (MR), Practice Simulation, Mechanical Engineering, DigitalÂ Laboratory, Teacher Abstrak: Keterbatasan akses laboratorium dalam pendidikan vokasi, khususnya pada bidang teknik mesin, sering menjadi kendala utama dalam memberikan pengalaman praktik yang aman dan relevan dengan kondisi industri. Guru SMK di Bontang menghadapi tantangan dalam menyediakan sarana pembelajaran praktik yang efektif dan efisien. Penelitian ini bertujuan untuk mengembangkan Laboratorium Mixed Reality (MR) sebagai solusi inovatif untuk simulasi praktik teknik mesin. MR Mixed Lab dirancang untuk memberikan pengalaman pembelajaran interaktif melalui teknologi realitas campuran, memungkinkan guru membimbing siswa dalam memahami konsep perakitan dan pembongkaran mesin tanpa risiko kerusakan peralatan atau cedera. Selain itu, penggunaan MR dapat menekan biaya operasional praktik serta meningkatkan frekuensi latihan dalam lingkungan belajar yang lebih realistis. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model ADDIE yang mencakup tahapan Analysis, Design, Development, Implementation, dan Evaluation. Proses pengembangan melibatkan analisis kebutuhan pengguna, desain sistem, pembuatan model 3D interaktif, serta pengujian efektivitas dengan melibatkan guru SMK. Data dikumpulkan melalui observasi, kuesioner, dan wawancara untuk mengevaluasi kemudahan penggunaan, efektivitas pembelajaran, serta tingkat keterlibatan pengguna. Hasil penelitian diharapkan dapat menghadirkan prototipe MR Lab yang relevan, layak, dan bermanfaat bagi pendidikan vokasiÂ Kata kunci: Mixed Reality (MR), Simulasi Praktik, Teknik Mesin, Laboratorium Digital, Guru